2009
DOI: 10.1080/00365520902929849
|View full text |Cite
|
Sign up to set email alerts
|

Palliative treatment of malignant gastroduodenal obstruction with metallic stent: prospective comparison of covered and uncovered stents

Abstract: Background. The placement of self-expandable metallic stents (SEMS) is known to be effective palliative treatment of malignant gastroduodenal obstruction. There are two types of SEMS Á covered and uncovered Á each with its own advantages and disadvantages. This study was conducted to compare between the clinical outcomes of covered and uncovered stents in patients with malignant gastroduodenal obstruction. Patients and methods. The study was conducted prospectively from January 1998 to June 2007 and 154 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
1
53
0
1
Order By: Relevance
“…Multivariate analysis revealed that the presence of a stent bridging the duodenal papilla [odds ratio (OR) =18.48; 95% CI, 2.298-148.48; P=0.006] was an independent predictor of acute pancreatitis. Table 2 shows the results of comparisons between CMS and UCMS in a prospective study and four randomized controlled trials (23)(24)(25)(26)(27). The technical and clinical success rates were similar between CMS and UCMS in all of these reports.…”
Section: Adverse Eventsmentioning
confidence: 89%
See 1 more Smart Citation
“…Multivariate analysis revealed that the presence of a stent bridging the duodenal papilla [odds ratio (OR) =18.48; 95% CI, 2.298-148.48; P=0.006] was an independent predictor of acute pancreatitis. Table 2 shows the results of comparisons between CMS and UCMS in a prospective study and four randomized controlled trials (23)(24)(25)(26)(27). The technical and clinical success rates were similar between CMS and UCMS in all of these reports.…”
Section: Adverse Eventsmentioning
confidence: 89%
“…The technical and clinical success rates were similar between CMS and UCMS in all of these reports. As an adverse event, the migration rate was significantly lower in the UCMS group in three of these five reports (23)(24)(25). However, Maetani et al reported that there was no significant difference in the migration rate between CMS and UCMS because the 15-mm uncovered portion at both ends of the UCMS prevented stent migration (26).…”
Section: Adverse Eventsmentioning
confidence: 96%
“…Stent re-intervention rates and stent patency and patient survival periods were similar in these two groups. 47 In the second study, retrospective in design, 40 technical/clinical success rates, stent patency time, and patient survival period did not differ between the covered (n=29) and bare (n=32) stent groups. Moreover, the rate of complications (including reobstruction, migration, bleeding, and stent fracture) did not differ significantly between the two groups.…”
Section: Covered Versus Bare Stentsmentioning
confidence: 99%
“…Two recent studies compared the clinical outcomes of covered and bare stents in the palliative treatment of malignant GOO. 40,47 A prospective, non-randomized study 47 found that the technical and clinical success rates were similar in patients receiving covered (n=70) and bare metal (n=84) stents. Stent migration was significantly more frequent in the covered than in the bare stent group (17.1% vs 0%; p <0.001), whereas tumor ingrowth was more frequent in the bare than in the covered stent group (16.6% vs 2.9%; p=0.0066).…”
Section: Covered Versus Bare Stentsmentioning
confidence: 99%
See 1 more Smart Citation